Analisis dan Visualisasi Data Kunjungan Wisatawan Mancanegara ke Indonesia Tahun 2024 Menggunakan Microsoft Power BI - Della Yunata; Randy Prandana (Universitas Mahkota Tricom Unggul, 2026)
Tourism is one of Indonesia’s national economic drivers, generating foreign exchange and creating employment. In 2024, international visitor (wisman) arrivals to Indonesia showed a significant post-pandemic recovery. This study aims to visualize and analyze 2024 international visitor arrival data sourced from the monthly Official Statistics News (BRS) and the annual publication of Statistics Indonesia (BPS), using Microsoft Power BI as a business intelligence tool. A quantitative descriptive method was applied to secondary data through the stages of data collection, data cleaning in Power Query, data modeling, visualization design, and interpretation. The results show that total arrivals throughout 2024 reached 13,902,420 visits, an increase of 19.05 percent compared to 2023 and the highest figure since 2020. Arrivals followed a seasonal pattern peaking in August (1.34 million visits); the market was dominated by visitors from Malaysia, Australia, Singapore, and China; entry points were concentrated at I Gusti Ngurah Rai Airport; and average visitor spending reached USD 1,391 per visit. Visualization through Power BI proved effective in revealing seasonal patterns, market dominance, and spatial concentration, providing a basis for strategic decision-making in national tourism development.